2022
DOI: 10.3390/antiox11091748
|View full text |Cite
|
Sign up to set email alerts
|

Free and Bound Phenolic Compounds Present in Orange Juice By-Product Powder and Their Contribution to Antioxidant Activity

Abstract: Interest in fruit/vegetable consumption is not always linked to a particular diet but rather derives from their high antioxidant activity (AOA), with potential health benefits provided, in part, by polyphenols. Although phenols can be found in free form (FP) or bound to plant tissues (BP), the experimental methodology most frequently used for the quantification of total phenols (TP) is based on the extraction of a portion of FP, which may justify the lack of correlation often found between them and AOA. In thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 32 publications
1
5
0
Order By: Relevance
“…OJC showed a water content higher than x w found in the literature for orange peel (72.5 g/100 g) [ 17 ], possibly because some pulp remained in the co-product used as raw material in this work after orange juice extraction. The freeze-drying process decreased ( p < 0.05) the water content by around 95%, to 3.12–4.46 g/100 g, similar values to previous studies [ 18 ] and of the same order of those suggested by other authors for quality freeze-dried products [ 19 ].…”
Section: Resultssupporting
confidence: 90%
“…OJC showed a water content higher than x w found in the literature for orange peel (72.5 g/100 g) [ 17 ], possibly because some pulp remained in the co-product used as raw material in this work after orange juice extraction. The freeze-drying process decreased ( p < 0.05) the water content by around 95%, to 3.12–4.46 g/100 g, similar values to previous studies [ 18 ] and of the same order of those suggested by other authors for quality freeze-dried products [ 19 ].…”
Section: Resultssupporting
confidence: 90%
“…The capacity of phenolic compounds to donate electrons or hydrogen atoms to free radicals or reactive oxygen species makes them known for their antioxidant properties. Important biomolecules like proteins, lipids, and DNA are shielded from oxidative damage by this mechanism, which also successfully neutralizes these dangerous substances (46). Previous studies that used different solvents or methods to assess the total phenol content of Juniperus phoenicea leaves or fruits can provide a basis for comparison with the current findings.…”
Section: Total Phenols Contentmentioning
confidence: 88%
“…The orange juice waste used as raw material was provided by the Belles Arts Sant Carles cafeteria of the Universitat Poltècnica de València (Spain) in February 2022. To obtain the co-product powder (CoP), the residue, after completely removing the central column and seeds, was crushed and emulsified (Robot coupe blixer2, Valencia, Spain) and water was added at a ratio of 1/0.38 to facilitate the process and create a homogeneous mixture [ 20 ]. Emulsification was carried out for 5 min per 750 g of residue.…”
Section: Methodsmentioning
confidence: 99%
“…The main flavonoids present in each fraction were analysed. In both cases, the method described by Camacho et al [ 20 ] was used. Briefly, 1 g of sample was extracted with MeOH at 30 °C and the filtrate obtained was extracted again with the same solvent but at 60 °C.…”
Section: Methodsmentioning
confidence: 99%